Willingness to Work with Older Adults in the Medical Field in Iran-2017 - Mollaei 1, Parisa; Abolfathi Momtaz 2, Yadollah; Mousavi Shirazi 1, Fatemeh; Delbari 2, Ahmad (Shahroud Journal of Medical Sciences, 2019)
-